Multi-proxy analyses of a peat bog on Isla de los Estados, easternmost Tierra del Fuego: a unique record of the variable Southern Hemisphere Westerlies since the last deglaciation - Björck, Svante; Rundgren, Mats; Ljung, Karl; Unkel, Ingmar; Wallin, Åsa (Quaternary science reviews, 2012)
We have analyzed an almost 14,000 year old peat sequence on the island of Isla de los Estados (55° S, 64° W), east of Tierra del Fuego, in the core of the Southern Hemisphere Westerlies. A multitude of methods have been used: high resolution 14C dating; detailed lithologic descriptions including humification degree; loss on ignition; magnetic susceptibility; bulk density; pollen and spore analysis and determination of Aeolian sand influx. By combining proxies for wind and precipitation we have been able to reconstruct how the westerlies have varied over time in the Atlantic sector of the Southern Ocean. It shows that this westerly wind belt was most intense at the onset of the record, 13,600-13,200 cal BP, coinciding with the mid to late part of the Antarctic Cold Reversal, followed by a gradual decline. At 12,200 cal BP the westerlies seem to have shifted to a position south of Tierra del Fuego and this phase, the calmest and driest period on the island throughout the sequence, ended at 10,000 cal BP when the westerlies moved equatorward again. Since then the westerlies have been present but with a variable impact on the 55° S latitude of the Atlantic. Mostly conditions have been fairly similar to today, but occasionally with a wider or narrower and/or weaker or stronger wind belt. At 7200 cal BP wind intensity began to increase and between 4500 and 3500 cal BP these southern latitudes experienced a distinct wind and precipitation maximum, both in terms of perseverance and intensity. Our results show a both wide and strong wind belt, with possible niveo-aeolian activity in Tierra del Fuego in winter, and possibly creating milder summers around the Antarctic Peninsula. In the later part of the Holocene, expansion-contraction phases of the wind belt, especially in winter, seem to have been a common phenomenon.
Online veröffentlicht: 25. April 2012
Gesehen am 19.02.2025